Virtual leadership in relation to employees' mental health, job satisfaction and perceptions of isolation: A scoping review - Efimov, Ilona; Rohwer, Elisabeth; Harth, Volker; Mache, Stefanie (Frontiers in psychology, 2022)
The significant increase of digital collaboration, driven by the current COVID-19 pandemic, is resulting in changes in working conditions and associated changes in the stress-strain perception of employees. Due to the evident leadership influence on employees' health and well-being in traditional work settings, there is a need to investigate leadership in virtual remote work contexts as well. The objective of this scoping review was to assess the extent and type of evidence concerning virtual leadership in relation to employees' mental health, job satisfaction and perceptions of isolation. A search was undertaken in five databases, PubMed, Cochrane Library, PsycINFO, PSYNDEX and Web of Science, as well as reference lists of included articles on 9th February 2021 and an update on 28th September 2021. The search strategy was limited to English, German and French language, peer reviewed journal articles published from January 2000 onwards. This scoping review was conducted in accordance with the JBI methodology for scoping reviews. The methodological quality of the included studies was assessed using the JBI critical appraisal tools. A narrative synthesis was conducted. Nineteen studies met the eligibility criteria for this review. Overarching review findings suggested a positive link between virtual leadership and well-being, job satisfaction, and a negative link to psychological strain, stress and perceptions of isolation of digitally collaborating employees. By mapping the available evidence on virtual leadership in relation to health and work-related employee outcomes, the review identified many research gaps in terms of content and methodology. Due to limited data, causal relationships were not derived. Future research is needed to examine the complex cause-and-effect relationships of virtual leadership in more detail.